Composting from Wastewater Sludge of Seafood Factory, Palm Empty Bunch and Lutoid of Rubber - Wandee, Sirinthrar; Satthasawat, Jantima; Chianwichai, Panadda; Petmee, Pongpat; Mahathaninwong, Narissara (Journal of Advanced Development in Engineering and Science, 2023)
An aerobic composting technique was used for a mixture of wastewater sludge from a seafood industry, empty-bunch palms, and sludge concentrate latex, which had a 1:1:1 ratio for a reactor 1 and a 2:1:1 ratio for a reactor 2. After 60 days of composting, temperature, moisture content, pH, electrical conductivity, organic matter, organic carbon, nitrogen, phosphorous (total P2O5), potassium (total K2O) and C/N ratio of the two reactors were determined. The results showed that the C/N ratios of the reactor 1 and 2 are 9.25 and 6.96, respectively. The percentage of N- P2O5- K2O were 2.68-24.90-1.28 and 3.28-18.11-1.18 for reactor 1 and 2, respectively. In addition, all of the parameters, except for moisture content, satisfied the standard of Department of Agriculture. Thus, the industrial waste products from this work can be further used as a soil-improving material.